Review of Various Hydroxyapatite Coating Methods on SS316L Foam for Biomedical Application - Syed Abu Bakar, Sharifah Adzila; Razak, Aisyah; Mat Isa, Najah; Ruslan, Nur Syazana; Selimin, Mohamad Ali (Journal of Advanced Mechanical Engineering Applications, 2021)
Metallic biomaterials such as 316L stainless steel (SS316L) are widely used as an implant to replace the function of damaged bone, especially in hip or knee applications. However, many of them fail during a short period or have complications. The biocompatibility issues are the main factor that caused this failure. Thus, coating the SS316L with bioactive and biocompatible material is one of the promising techniques to enhance the biocompatibility and lifetime of the implant. This paper provides an overview of the SS316L foam coated hydroxyapatite (HA). Various methods of HA coating such as sol-gel, dip coating, electrophoretic deposition, plasma spraying, and pulse laser deposition applied on SS316L foam and their coating characteristics were investigated based on recent literature. SS316L foam coated HA using different coating methods were compiled and their basic properties were reported. Therefore, this paper will benefit future works on SS316L foam coated HA in a biomedical application.